Factors Associated with the Selection of Contraception Devices in Fertile Age Couples in Tabang Village Bolong Village North Walenrang Districh Luwu Regency in 2016 - Hera Wati Ramli (State Islamic University of Sunan Ampel, 2019)
Factors Associated with the Selection of Contraception Devices in Fertile Age Couples in Tabang Village, Bolong Village, North Walenrang District, Luwu Regency, 2016. This study aims to analyze the factors related to respondents. Where the theory that explains there are several factors that can influence the selection of the tools that most influence are fundamental things. This research was conducted in Tabang Hamlet, Bolong Village, North Walenrang District, Luwu Regency using cross- sectional tudy method. The population in this study were 30 couples in the suburbs (PUS) who used contraception in Tabang Village, Bolong Village, North Walenrang District, Luwu Regency. The sampling technique in this study used total sampling. Data collection through data demographics and questionnaires, data analysis using Chi-Square Test. The results of the study showed that most respondents chose injectable contraceptive methods. There is a very effective relationship between the values ​​with contraceptive selection p value = 0.00 (5 0.05), there is a relationship between knowledge and with the choice of toxicity p value = 0.01 (5 0.05), and there is a relationship that means between education with contraceptive selection p-value = 0.01 (≤ 0.05). From this study, knowledge and education were the most effective factors in the factors related to the selection of contraception devices in fertile age couples (Pus) in Tabang Village, Bolong Village, North Walenrang District.